A descriptive study investigating cervical spine injuries, cervical muscle weakness, posture and establishing norms for senior rugby players in Gauteng - Etsebeth, Chantelle (My University, 2020)
BACKGROUND: Rugby is one of the most popular sporting types around the world with a total amount 2.82 million players in 2015 and 3.2 million in 2016. The association between cervical spine muscle weakness, range of motion, and an increased risk for cervical injuries needs to be established, particularly in a South African context, where injury incidence seems to be higher compared to global incidence. The occurrence of these cervical spine injuries has the potential to have a major influence on the quality of life, of rugby players following injury as well as a potential loss of life. AIM: This study was aimed to identify the prevalence and frequency at which cervical spine injuries occurred within a South African rugby population. It also aspired to identify whether weak neck musculature, limitation in cervical range of motion, and poor posture are associated with an increased risk for cervical spine injuries. This study also aimed to establish sport-specific norms for neck strength for this population, which has the potential to aid in return to sport clearance. OBJECTIVES: 1. To determine the occurrence of cervical spine injuries amongst senior rugby players. 2. To determine the posture of senior rugby players. 3. To determine the cervical range of motion of senior rugby players. 4. To determine isometric neck strength of senior rugby players. 5. To determine if there is a relationship between cervical muscle weakness and poor posture. 6. To determine sport-specific strength norms, for the cervical spine, for senior rugby players. METHODS: A descriptive, cross-sectional study were a total of 139 male (mean age 20.42 ± 3.29 years) senior rugby players participated in this study. A personal detail and injury screening questionnaire, and Neck Disability Index (NDI) questionnaire was completed prior to testing taking place. The Multi-Cervical Unit (MCU) was used to test the cervical range of motion as well as isometric neck strength in multi-plane patterns of movement for the players. Cervical ROM was tested in flexion, extension, lateral flexion, and rotation. This was followed by cervical spine strength tests for flexion, extension, and lateral flexion. Angles used were neutral (0°), 25° and 45° for left and right. A Mc Neymar’s, Fisher’s exact and a Pearson’s correlation test was used to draw comparisons. Statistical significance of 95% (P < 0.05) was deemed as acceptable. RESULTS: All 139 participants were included in the final analysis of the study. Injury occurrence rate: 83 players stated that they had previously sustained a concussion of which the majority were classified as mild (63%) (n = 52 players). Posture: A mean overall posture rating score of 7.38 ± 1.05 (out of 10) was recorded for the players. The anatomical body site indicating the highest/best overall score was the hips (8.35 ± 2.36 out of 10) while the lowest score was found for the ankle region (6.26 ± 2.26 out of 10). Cervical ROM: Comparisons made with the general population norms indicated that the population tested below or less than the specified cervical ROM norms for flexion 4.32% (n = 6), extension 15.83% (n = 22), left lateral flexion 7.19% (n = 10), right lateral flexion 4.32% (n = 6), left rotation 27.34% (n = 38), and right rotation 25.18% (n = 35). Isometric neck strength: Seventy-two percent (n = 100) of the participants identified that they had never participated in neck strengthening protocols throughout their rugby careers. Neutral cervical neck flexion for senior rugby players indicated an average of 13.26 ± 5.78 (kg) with 60.43% (n = 84) of the players testing above the general population norm. Strength measured for flexion at 25° for the left and right side indicated averages of 12.07 ± 4.79 (kg) and 11.80 ± 4.23 (kg) respectively. Strength at 25° for left and right, the bulk of players tested stronger than the population norm (left n = 84; right n = 81). Flexion at 45° left and right showed an average of 11.28 ± 3.71(kg) and 11.56 ± 5.41(kg), with most players also measuring stronger than the general population norm, (left n = 82; right n = 84). Neck strength and posture: a statistical significance was found between posture and cervical: flexion at 25º left and right; 45º left and right; neutral extension (0 º); extension at 25º left and right; extension at 45º left and right; Left and right lateral flexion at neutral (0º); left and right lateral flexion at 25º, and left and right lateral flexion at 45º. The rating of the neck, hips, spine, and lower back were the four body regions that identified the correlation results. Overall posture rating score also resulted in significant results for four of the angles tested. Sport-specific strength norms: Strength norms were developed for the population. CONCLUSION: This study concluded that there is a positive association between the limitations in cervical ROM and posture abnormalities, and an increased risk of cervical spine and head injuries in senior South African rugby players. It also found that even though the majority of rugby players tested above the general population norm for cervical spine strength, at least one of the angles tested, fell below the general population norm which for the biggest majority was for cervical extension. No significant association was found between poor posture and strength and an increased risk of obtaining cervical spine- and head injuries in this population.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Medicine in the branch of Biokinetics to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020